Neither Cold nor Hot but Lukewarm: Rethinking the Temperature Metaphor in Revelation 3:15–16 - Mark Wilson (Tyndale Bulletin)
The temperature metaphor in Revelation chapter 3 is used by Jesus to admonish the Laodiceans regarding their spiritual condition. The prevailing understanding of the metaphor centres around the city’s deficient water system, an interpretation no longer tenable because of recent archaeological discoveries. A subsequent interpretation of the metaphor was proposed, but this too is not persuasive. After briefly reviewing the archaeological finds related to Laodicea’s hydrological situation and critiquing the alternate proposal, a fresh hypothesis is introduced for interpreting the temperature metaphor by setting it amidst the material culture of Laodicea and the other six cities in Asia, specifically bathing in a Roman bathhouse.